2012
DOI: 10.1161/strokeaha.112.667535
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Surgery for Spontaneous Supratentorial Intracerebral Hemorrhage

Abstract: Background and Purpose— There has been a nonstandard surgical procedure and extensive international controversy in minimally invasive surgery (MIS) for the management of spontaneous supratentorial intracerebral hemorrhage. This meta-analysis assessed the effectiveness of MIS as compared with other treatment options, including conservative medical treatment and conventional craniotomy, in patients with supratentorial intracerebral hemorrhage. Methods— Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
121
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(129 citation statements)
references
References 44 publications
1
121
1
6
Order By: Relevance
“…19 These authors reported a highly significant reduction in the end points of both death and dependence and death alone at the end of study follow-up. They determined that ICH patients with smaller hemorrhages (25-40 cm 3 ) and good presenting clinical status (Glasgow Coma Scale ≥9) were the most likely to benefit from MIS.…”
Section: Meta-analyses Of Mis Trialsmentioning
confidence: 94%
See 1 more Smart Citation
“…19 These authors reported a highly significant reduction in the end points of both death and dependence and death alone at the end of study follow-up. They determined that ICH patients with smaller hemorrhages (25-40 cm 3 ) and good presenting clinical status (Glasgow Coma Scale ≥9) were the most likely to benefit from MIS.…”
Section: Meta-analyses Of Mis Trialsmentioning
confidence: 94%
“…Although MIS for ICH is a routine clinical procedure in the Far East, with over 150 000 cases being performed per year, it is much less common in North America and Europe. 19 The current American Heart Association guidelines provide a Class IIb, Level of evidence B recommendation for the minimally invasive surgical treatment of ICH. …”
Section: Meta-analyses Of Mis Trialsmentioning
confidence: 99%
“…Tokiu atveju stebimas didžiausias šio gydymo metodo efektyvumas [22]. Tuo tarpu didesnę kraujosruvą dažniausiai siūloma šalinti atviruoju būdu, o mažesnes dažnai galima palikti ir konservatyviam gydymui.…”
Section: Aptarimas Intracerebrinės Kraujosruvos Chirurginis Gydymasunclassified
“…Dėl šių priežasčių siūloma hematomos pašalinimą atlikti praėjus mažiausiai 6 val., bet ne daugiau nei 72 val. nuo simptomų pasireiškimo pradžios [22].…”
Section: Aptarimas Intracerebrinės Kraujosruvos Chirurginis Gydymasunclassified
“…MIS is a safe and practical technique in treating ICH. Patients with ICH may be benefit more from MIS than other treatment options [6][7][8][9]. Although MIS could effectively evacuate blood clot and reduce the brain damage following ICH, but does not completely remove the erythrocytes and cytotoxic substances which extravasate into the adjacent brain [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%